Motivasi anak bermain: Peran pendidik dan orang tua dalam mendukung perkembangan anak usia dini - Asmah, Ayu; Syamsudin, Amir (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2025)
Play is a fundamental early childhood activity in supporting development in physical, cognitive, language, social-emotional and spiritual aspects. This article discusses the role of educators and parents in supporting children's motivation to play in supporting optimal early childhood development. This research uses the literature review method to analyze various data sources from relevant scientific journals. Based on the findings, PAUD educators have an important role in designing learning strategies that integrate the principle of “playing while learning”, using innovative learning methods, such as storytelling methods and traditional games. In addition, the role of parents as educators, motivators and facilitators at home greatly supports children's motivation to play. Collaboration between PAUD educators and parents is a major factor in creating a conducive learning environment and stimulating children's enthusiasm for learning. The development of digital technology also offers opportunities for the use of educational games as an interesting learning medium, although their use needs to be accompanied by parents to prevent negative impacts. Overall, children's motivation to play can be strengthened through the active role of educators and parents, and good collaboration between the two. This is very important to support optimal early childhood development, both in the school and family environment.